Management guidelines for venous thrombosis in the lower limbs according to the European Society of Vascular Surgery 2021. - Gomez-Vera, Carlos Eduardo (2022)
Deep vein thrombosis (DVT) is caused by a fibrin thrombus which reduces the blood supply to the surrounding tissues. Within the complications reported in the literature we find pulmonary embolic events (PE), which, once generated, develop great repercussions on the survival of those who suffer from them. The diagnosis is made in a multidisciplinary manner, using measures such as the Wells score, D-dimer measurement, computed venography, among others. The European Society of Vascular Surgery in its 2021 clinical practice guideline, mentions the appropriate way to make the diagnosis, taking into account the risk factors, the classification according to the triggering factor and the currently available images. Likewise, it indicates the treatment that should be offered based on the location of the thrombus and what pharmacological and non-pharmacological measures can be chosen in different clinical scenarios. The following review highlights the key and most relevant aspects to take into account for the management of patients with this entity.